Capital Depreciation in the Postwar Period: Automobiles - Wykoff, Frank C. (The Review of Economics and Statistics, 1970)
T O measure a nation's wealth, an industry's productive potential or the consumption of a durable stock, we must be able to add machines with different characteristics and different vintages to form an aggregate. Ideally, such a measure would change with machinery deterioration and obsolescence but not with pure price level changes which leave the use of the machinery the same. The aggregation task would be easier if we had information about the nature of depreciation. For example, if depreciation is a constant rate, and that rate remains the same over time, then the aggregate is a simple weighted average of the component machines, the weights being derived from the known depreciation rate. This model is not uncommon, yet its assumptions are clearly restrictive. It would be very useful if there were sufficient empirical evidence pertaining to the nature of depreciation patterns to either confirm or reject such a simple model. It is the intent of this paper to provide some of that evidence. One natural approach to studying decay of capital is to study the in-use cost of machines as they age. Depreciation values could be estimated from changes in rental prices throughout a machine's life. In the absence of welldeveloped rental markets, however, resale values would yield approximations of the remaining value of machinery after a period of use. This paper constructs actual depreciation figures for automobiles from purchase prices, and studies assumptions and hypotheses about the relationship between new and used machinery. In particular, three assumptions are common. First, it is often assumed that depreciation patterns remain fixed over time. For this assumption to be valid, any technological change must be either nonexistent or smooth. There can be no sudden, dramatic innovations, since these would change the nature of depreciation schemes. Similarly, it is often assumed that machinery of the same type depreciates in the same fashion. This assumption will also be studied. The third and most common assumption is that equipment depreciates at a constant rate.' This is a very useful assumption, since it greatly simplifies the relationship between new and used pieces of equipment. These assumptions will be tested for automobiles using figures for nineteen different makes from 1950 to 1969.